(untitled) (Bangladesh Journal of Neurosurgery, 2022)
An 11 months old male child, with congenital HCP presented with extrusion of shunt tube form the anus after defecation. He was managed by VP shunt 8 months back; 6 months later lower end was revised for obstruction. Lower end of shunt exteriorized and the distal end was cut and pulled out per rectally. Later ETV done patient discharged uneventfully.Key words: VP Shunt, Trans anal, Extrusion, Management, Outcome. Bang. J Neurosurgery 2022; 11(2): 138-140